2019
DOI: 10.1016/j.imr.2019.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A naturalistic study of herbal medicine for self-reported depression and/or anxiety a protocol

Abstract: Background Mental health conditions including anxiety and depression account for around 8% of the global disease burden. Anxiety and depression often coexist and impose a high individual and social burden. Patients with mental and behavioural conditions may be at increased risk of co-morbidities and are often high health-care utilisers. Herbal medicine is estimated to be used by up to 80% of the worlds population, and by 22% of Australian women seeking care for depression. The holistic and tailore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 44 publications
0
2
0
1
Order By: Relevance
“…Bu nedenlerle anksiyete dahil olmak üzere çeşitli psikiyatrik hastalıkları tedavi etmek için tıbbi bitkilerin kullanımında önemli bir artış görülmektedir [16]. Bu ürünler toplumda, sentetik ilaçlara göre yan etkisi daha düşük veya tedavi edici özelliği daha yüksek ve daha güvenli alternatifler olarak algılanabilmektedir [16,17]. Fakat doğru ürün, ancak doğru zamanda, uygun dozda ve uygun formülasyonda kullanıldığı takdirde konvansiyonel tedaviyi destekleyici bir rol üstlenebilmektedir.…”
Section: Anksiyete Bozukluğuunclassified
“…Bu nedenlerle anksiyete dahil olmak üzere çeşitli psikiyatrik hastalıkları tedavi etmek için tıbbi bitkilerin kullanımında önemli bir artış görülmektedir [16]. Bu ürünler toplumda, sentetik ilaçlara göre yan etkisi daha düşük veya tedavi edici özelliği daha yüksek ve daha güvenli alternatifler olarak algılanabilmektedir [16,17]. Fakat doğru ürün, ancak doğru zamanda, uygun dozda ve uygun formülasyonda kullanıldığı takdirde konvansiyonel tedaviyi destekleyici bir rol üstlenebilmektedir.…”
Section: Anksiyete Bozukluğuunclassified
“…The perception that medicinal plants are natural and therefore "safe" in recent years has led to an increase in the use of plants for treatment (Coghlan et al, 2015). Studies showed that medicinal plants are an important therapeutic resource especially for self-treatment (Anheyer et al, 2018) and can be considered as complementary medicines due to their positive effects on mental illnesses (Casteleijn et al, 2019;Sahoo & Brijesh, 2019). The therapeutic effects of medicinal plants encourage people to use herbal medicines to cure physical and mental illnesses (Achour et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Many herbal medicines have long been used as antibacterials, attractants (Khoshkharam, Shahrajabian, Sun, & Cheng, 2019; Soleymani & Shahrajabian, 2018), and also considered to be efficacious alternatives to antibiotics, vaccines, chemicals and synthetic compounds (Ogbaji, Shahrajabian, & Xue, 2013; Shahrajabian, Sun, & Cheng, 2019c, 2019d; Soleymani & Shahrajabian, 2012). Herbal medicine can be considered as supplementary drugs for their positive influence on both anxiety and depression (Abbo, Ekblad, Waako, Okello, & Musisi, 2009; Casteleijn, Steel, Bowman, Lauche, & Wardle, 2019; Ngoma, Prince, & Mann, 2003; Sahoo & Brijesh, 2019). Traditional herbal medicines can be combining herbal mixtures or single plant application (Shahrajabian et al, 2020a,b,c; Sun, Shahrajabian, & Cheng, 2019a, 2019b).…”
Section: Introductionmentioning
confidence: 99%